Caregiver capabilities: Healthcare interventions for children with developmental disabilities - Lumka Magidigidi-Mathiso; Jose Frantz; Gerard C. Filies (African Journal of Disability)
Background: Developmental disabilities (DDs) involve impairments affecting children’s abilities, impacting development and necessitating specialised care. Many caregivers face challenges caring for these children, lacking access to supportive healthcare interventions. Addressing this issue aligns with United Nations (UN) goals for ensuring access to quality services for children with disabilities and their caregivers.